Pengaruh Sharia Compliance, Struktur Modal, dan Dana Pihak Ketiga terhadap Profitabilitas (Studi Empiris pada Bank Umum Syariah di Indonesia yang Terdaftar di Ojk 2016-2023) - Yunita, Wanda; Badina, Tenny; Fatoni, Ahmad (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This research aims to look at the variables Islamic Income Ratio, Profit Sharing Ratio, Zakat Performing Ratio, Capital Structure and Third Party Funds in influencing ROA Profitability. The population in this research is Sharia Commercial Bank companies registered with the OJK for the 2016-2023 period. The data used in this research is panel data from 9 selected companies, with a total sample of 72. The sampling technique uses purposive sampling. The analysis technique uses the panel data regression method which is processed using Eviews 12.0. The results of the research specifically show that the Zakat Performing Ratio and Capital Structure have a positive and significant influence on the profitability of Islamic commercial banks. Meanwhile, the Islamic income ratio, profit sharing ratio, voluntary disclosure and third party funds have no effect on the profitability of Islamic commercial banks. The research results simultaneously show that the variables Islamic income ratio, profit sharing ratio, zakat performing ratio, voluntary disclosure, capital structure and third party funds have an influence on the profitability of Islamic commercial banks. Keyword: Capital Structure, Islamic Income Ratio, Profit Sharing Ratio, Profitability, Third Party Funds, Voluntary Disclosure, Zakat Performing Ratio